Crimmigration in Slovenia - Bajt, Veronika (Dve domovini, 2019)
The article discusses "crimmigration" (i.e. the criminalization of migration) in Slovenia. It evaluates elements of crimmigration in the legal framework, institutions and policies. The analysis of the framing of the topic at the normative level of institutions is accompanied by an examination of the implementation of specific procedures in practice. An exploration of policies and expert opinions is combined with an analysis of the effects that crimmigration has on migrants. Corroborated with the migrants' experience with crimmigration measures, the article concludes that migration policy in Slovenia is becoming stricter and progressively headed in the direction of increased criminalization of migration.
Keywords: asylum; azil; begunci; crimmigration; kazensko pravo; krimigracije; kriminalizacija; migracije; migracijska politika; migration; Slovenia; Slovenija